Putting the sting back in STING therapy: novel delivery vehicles for improved STING activation - Sina Khorsandi; Kristin Huntoon; Jacques Lux (Frontiers in Chemical Biology, 2024)
Engaging the immune sensing Stimulator of Interferon Genes (STING) pathway has emerged as a potentially powerful approach to cancer therapy. However, current STING agonists lack stability and specificity, resulting in toxic adverse effects and disappointing patient outcomes. Therefore, novel delivery vehicles are needed to mitigate negative results and improve the efficacy of STING agonists. Here we discuss innovative particle-based strategies and how they have increased the therapeutic results seen with STING agonists. We review ultrasound-responsive vehicles, pH-responsive particles, inorganic particles, carriers for extended release, and particles that act as both STING agonists and/or drug carriers. Further optimization of these strategies can potentially enable the clinical use of STING agonists for cancer therapy.